Flying Time Of Quadcopter Based On Green Composites Material - Mastariyanto Perdana; Nurzal Nurzal; Syahrul Firdaus; Rozi Saferi (Jurnal Teknik Mesin (JTM), 2018)
Application of green composites material is aerial egineering. Advantages of green composites material are lightweight and relatively strong. This reason that makes green composites can be applied in Unmanned Aerial Vehicle (UAV). In this study, material of quadcopter frame was composites material that made of waste material from styrofoam, bagasse and eggshell. Styrofoam was used as binder of composite material. Bagasse and eggshell was used as reinforcement in green composite material. The investigation focused on effect of volume fraction on flying time of quadcopter that made of green composites material. This study showed that addition of eggshell powder in composites up 25% by volume fraction, result in decreasing the flying time of quadcopter. Addition of eggshell powder in composites up 25% by volume fraction,  result in decreasing the porous of green composite. Porous structure affect the flying time of quadcopter based on green composite materials that made of waste material from styrofoam, bagasse and eggshell. Green composite based on styrofoam, bagasse and eggshell can be applied in Unmanned Aerial Vehicle (UAV) materials.